BERBAUR TANPA KEHILANGAN IDENTITAS: PENDIDIKAN MORAL ETIS MENUJU KEDEWASAAN - Meysi Siahaan; Sarah Sirait; Septina Rumiris Sitorus; Septina Silaen; Windi Yohana Tambunan; Damayanti Nababan (Pusat Riset dan Inovasi Nasional, 2022)
Based on success of a person, characteristic becomes a determinant in actualizing it in everyday life. Even someone who has a high level of intelligence can be said to be successful if he has a strong character in himself. Character has a strong influence in life, a person sometimes has a character crisis caused by a lack of awareness or ignorance about himself including his own character, and denial of self-identity. This crisis can happen to anyone, from children to adults. In early adulthood a person will think more logically and logically everything including the logic of the Creator. It is in this early adult that a person must complete the Christian identity that is held to be applied in his life. What becomes a Christian identity is creating a peaceful and harmonious life in society, loving one another, being sincere towards others, and being sincere in dealing with things, these things are the fundamentals of Christian identity. Jesus Christ who is the Christian's role model and the Bible that is the role model must be the basis of Christian identity, Jesus is the teacher and the Bible is the source of learning. This Christian identity will become stronger as a person experiences growth in faith, especially someone who is in a phase towards maturity or commonly called early adulthood.